Leaching/Bioleaching and Recovery of Metals - Laura Castro (MDPI AG, 2021)
Hydrometallurgical processes for metal extraction are becoming more and more popular as average ore grades are declining and huge tonnages of tailings and recycle materials containing valuable metals are being accumulated all around the world [...]